Pengaruh Fraud Triangle Terhadap Kecurangan Laporan Keuangan - Mella Handayani (LPPM Universitas Multi Data Palembang, 2023)
This Study aims to determine the effect of the fraud triangle on fraudulent financial statement incompanies listed on the IDX for the 2017-2020 period. The independet variables in the fraud trianngle consist ofpressure(financial target), which is proxied by ROA, opportunity(ineffective monitoring) is proxied by BDOUT, andrationalization is proxied by TATA. The dependent variable in this study is financial statement fraud which isproxied using the Altman Z-Score. The object of this research is an state-owned enterprises company listed on theindonesia stock exchange. The approach used in this research is associative. The data used in this research issecondary data. The technique used in collecting data in this tudy uses documents that can support the research.The analysis technique used in this syudy uses descriptive statistics, classical assumption test, coefficientofdetermination, hypothesis testing, and analisys multiple linear regression. The results in this study simultaneouslyfinancial targets, ineffective monitoring, and rationalization have a significant effect on financial statement fraud.The results of the partial test conducted by financial targets and rationalization have no effect on financialstatement fraud, while ineffective monitoring have a significant effect on financial statement fraud.